A Survey on Different Interoperability Frameworks of SOA Systems Towards Seamless Interoperability - M. Ibrahim, N.; Hassan, M.F. (2010)
Service Oriented Architecture (SOA) plays many important roles for resource sharing and manipulating interconnected data in heterogeneous geographic distributed environments. Interoperability is two or more systems which is able to communicate, share, and exchange the resources with no need to know how each other works, but in the same time both need to have some common specifications to provide a reliable connection with no errors or misunderstanding. Many research works have been conducted to solve different interoperability issues for specific domains such as resource management, enterprise system and healthcare sector. Different development styles may lead to breakdown or interruption of communication. This paper examines and reviews studies related to interoperability frameworks. We found that different domains will have different types of interoperability frameworks. We argued that future research in this area is needed to consolidate and address interoperability issues which are required for a standard seamless framework between multi SOA platforms.